Complex permittivity measurements at Ka-Band using rectangular dielectric waveguide - Abbas, Z.; Pollard, R.D.; Kelsall, R.W. (Institute of Electrical and Electronics Engineers, 2001)
The rectangular dielectric waveguide (RDWG) technique has been developed for the determination of the dielectric constant of materials from effective refractive index measurements in the Q and W bands. This paper describes the use of an optimization method in conjunction with the RDWG technique for the determination of both the dielectric constant and loss tangent of materials at Ka-Band. The effect of the uncertainty in the measured sample thickness is presented.